fx-b=h

Simple and best practice solution for fx-b=h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for fx-b=h equation:


Simplifying
fx + -1b = h

Reorder the terms:
-1b + fx = h

Solving
-1b + fx = h

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-1fx' to each side of the equation.
-1b + fx + -1fx = -1fx + h

Combine like terms: fx + -1fx = 0
-1b + 0 = -1fx + h
-1b = -1fx + h

Divide each side by '-1'.
b = fx + -1h

Simplifying
b = fx + -1h

See similar equations:

| (2x+9)(x-6)=-2(6-x) | | 4.95+11.95d=64.70 | | -40=-8(-8b+5) | | 4t+6t= | | (17y)-(15y)= | | 4(2x-1)-5x=2+4(3-x) | | 17y-15y= | | w+4(w+3)=-12 | | (3y+1)(y-1)=(y+5)(2y-5) | | 30-2s=4 | | x=2y-4 | | 17+11x=-19x-25 | | 3y^2-23y-8=0 | | 3x-5(2-4x)=18 | | x^2-36y^2= | | -y=x-3 | | -40-8m=8(1+2m) | | (4x+5)(x-2)=(2x-1)(2x+2) | | 3x+90=180 | | 4x(-6x+2)=23 | | 24=-6-2(3x-6) | | 4x(7x+2)=23 | | 3x+60=180 | | X-9+5x=2x-3 | | -12-4(-5*3)= | | 4x(-7x+2)=24 | | 4x(-7x+2)=23 | | Log^6(1-x)=4 | | y-2=3(x-1) | | x+(.66*x)=120 | | (-8)(-3)-4(-6)= | | 21/70=3/10 |

Equations solver categories